DETEKSI KECURANGAN LAPORAN KEUANGAN DALAM PERSPEKTIF FRAUD TRIANGLE (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK , 2018-2020) - RUSDI RUSDI; ELVINA SETIAWATI; DINI ADENTARI (JURNAL ILMIAH SIMANTEK, 2023)
This study aims to empirically examine the effect of the fraud triangle on financial statement fraud in manufacturing companies in the consumer goods industry sector on the Indonesia Stock Exchange (IDX) for the 2018-2020 period. The variables used in this study are financial stability (X1), personal financial need (X2), ineffective monitoring (X3) and earnings management (Y). The type of research used in this study is associative. The population of this study is 68 consumer goods industrial sector companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period. The sample in this study were 120 companies which were taken using purposive sampling. The results show that financial stability (X1) has no effect on financial statement fraud because when the company's financial condition is stable or unstable, management does not always manipulate financial statements, personal financial need (X2) does not affect financial statement fraud because the level of share ownership by insiders will not affect the company's earnings management. ineffective monitoring (X3) has no effect on financial statement fraud because it is not the board of commissioners that affects earnings management, but the quality of the board of commissioners that affects earnings management. This shows that the possibility of forming an independent audit committee is only to comply with regulations.